An Institution-Based Assessment of Students' Hand Washing Behavior. (28th December 2019) - Mbouthieu Teumta, Grace M.; Niba, Loveline L.; Ncheuveu, Nkwatoh Therese; Ghumbemsitia, Mary-Teresia; Itor, Paul O.B.; Chongwain, Paul; Navti, Lifoter K.
Abstract : Background . Hand hygiene is cost-effective and has been recognized as an effective measure in the control of communicable diseases. The main aim of this study is to evaluate the hand washing knowledge, practices, and skills of students in both private and public institutions of higher learning. Methods . This was an institution-based cross-sectional study that included a mix of 577 university students from different disciplines (49.6% males and 50.4% females) with a mean age of 21.8 ± 3.5 years. Departments were selected at random, and the quota sampling technique was used to select the study participants. Hand washing knowledge, practices, and skills scores were assessed using a structured questionnaire. The differences in scores were further quantified across different factors using multiple quantile regression analysis. Results . The prevalence of hand washing with soap was 10.7%. Also, the majority of the study participants (75.2%) had a poor hand washing practices score. Age ≥29 years was associated with a 6.3% lower median hand washing knowledge score (p = 0.039 ). Also, being in the public institution was significantly associated with 6.3%, 36.0%, and 10.0% lower median hand washing knowledge (p = 0.021 ), practices (p < 0.001 ), and skills (p = 0.025 ) scores, respectively. In addition, being a medical student (p = 0.029 ) and washing hands ≥ six times a day (p = 0.008 ) were significantly associated with an increase in the median hand washing knowledge score of 6.3% and 18.7%, respectively. Conclusions . Educational interventions need to be carried out to create awareness of the importance of hand washing and also to enhance the hand washing knowledge, practices, and skills of university students.